KELEMBAGAAN PETANI: PERAN DAN STRATEGI PENGEMBANGAN KAPASITASNYA - ANANTANYU, SAPJA (Universitas Sebelas Maret, 2011)
The existence of farmer’s institutions become important at agricultural development in a country. This institutions are necessary in order to improve the competitiveness of farmers in developing agribusiness system in Indonesia. Strong farmer institutions are increasingly necessary in the of globalization and free trade era. Farmer institutions are as a means of expanding the capacities of farmers toward self-relience. This paper describes two things, namely: (1) Urgency of the existenceof farmer institutions, and (2) strategy in the development of farmer’s institutions.